Risk factors for both retrospective and prospective shoulder injuries in water polo - Croteau, F.; Robbins, S.; Pearsall, D.; Paradelo, D. (British Journal of Sports Medicine, 2021)
Introduction The main objective was to estimate whether previous injury, changes in strength, range of motion (ROM) or upward scapular rotation (UR) are related to new shoulder injuries in water polo players.